NEEDS ANALYSIS OF A LOCAL-WISDOM-BASED FICTION TEXT E-MODULE FROM KENDAL FOLKTALES FOR FIFTH-GRADE ELEMENTARY STUDENTS - Dewi Arum Sari; Asropah Asropah; Nazla Maharani Umaya (Edukasi Islami : Jurnal Pendidikan Islam, 2026)
This study aims to analyze the need for a local-wisdom-based fiction text e-module adapted from Kendal folktales for fifth-grade elementary school students. The study is motivated by the limited integration of local cultural contexts and Kendal folktales in fiction text learning, resulting in learning activities that are not yet fully contextual, meaningful, or closely connected to students’ socio-cultural experiences. A descriptive qualitative approach supported by descriptive quantification was employed, focusing on the needs analysis stage within research and development, as commonly applied in educational needs assessment studies (Wanto et al., 2020; Okpatrioka, 2023). The research subjects consisted of fifth-grade teachers and students from two public elementary schools in Kendal Regency. Data were collected through textbook observation, teacher needs questionnaires, and student needs questionnaires. The findings indicate that the textbooks currently used have not integrated Kendal folktales or local wisdom values into fiction text learning. The needs analysis further reveals a demand for contextual fiction text teaching materials that incorporate Kendal folktales and local wisdom and are presented in digital form. The local wisdom values embedded in Kendal folktales also have the potential to strengthen students’ character, moral awareness, and religious values in alignment with the principles of Islamic education when integrated contextually into learning (Ibnu Sholeh et al., 2025; Najiyah et al., 2024). These findings affirm the need to develop a local-wisdom-based fiction text e-module to support contextual, literacy-oriented, and value-based Indonesian language learning in elementary schools. This study is limited to the needs analysis stage; therefore, future research is recommended to focus on the development, validation, and effectiveness testing of the proposed e-module.